Netnography study on Chinese business success in Indonesia - Puspita, Rosana Eri; Muslih, Muhammad (Nur Science Institute, 2023)
Chinese businesses can thrive in Muslim-majority countries like Indonesia. This study aims to analyze Chinese business people's success and netizen behavior on content about the success of Chinese business people in Muslim-majority countries. Qualitative methods with a netnographic approach were used in this study. The data extraction process uses Newsletter and NVIVO software. The sample was taken from 12,451 netizen comments from 5 selected video content on the YouTube application. This study's results are about words often discussed in the comment column, netizen sentiments, and NVIVO coding results regarding netizens' perspectives on the principles of Chinese business success in Indonesia. The novelty of this research is that it offers an assessment using netnography and analyzing netizen behavior toward the success of business Chinese. The researcher suggested that further research can discuss the key to business success in other countries because each nation has values influencing business running.